Deficiencies in the Mitochondrial Electron Transport Chain Affect Redox Poise and Resistance Toward Colletotrichum higginsianum - McCollum, Christopher; Geißelsöder, Sonja; Engelsdorf, Timo; Voitsik, Anna Maria; Voll, Lars M. (Frontiers in Plant Science, 2019)
To investigate if and how the integrity of the mitochondrial electron transport chain (mETC) influences susceptibility of Arabidopsis toward Colletotrichum higginsianum, we have selected previously characterized mutants with defects at different stages of the mETC, namely, the complex I mutant ndufs4, the complex II mutant sdh2-1, the complex III mutant ucr8-1, and a mutant of the uncoupling protein ucp1-2. Relative to wild type, the selected complex I, II, and III mutants showed decreased total respiration, increased alternative respiration, as well as increased redox charge of the NADP(H) pool and decreased redox charge of the NAD(H) pool in the dark. In the light, mETC mutants accumulated free amino acids, albeit to varying degrees. Glycine and serine, which are involved in carbon recycling from photorespiration, and N-rich amino acids were predominantly increased in mETC mutants compared to the wild type. Taking together the physiological phenotypes of all examined mutants, our results suggest a connection between the limitation in the re-oxidation of reducing equivalents in the mitochondrial matrix and the induction of nitrate assimilation into free amino acids in the cytosol, which seems to be engaged as an additional sink for reducing power. The sdh2-1 mutant was less susceptible to C. higginsianum and did not show hampered salicylic acid (SA) accumulation as previously reported for SDH1 knock-down plants. The ROS burst remained unaffected in sdh2-1, emonstrating that subunit SDH2 is not involved in the control of ROS production and SA signaling by complex II. Moreover, the ndufs4 mutant showed only 20% of C. higginsianum colonization compared to wild type, with the ROS burst and the production of callose papillae being significantly increased compared to wild type. This indicates that a restriction of respiratory metabolism can positively affect pre-penetration resistance of Arabidopsis. Taking metabolite profiling data from all investigated mETC mutants, a strong positive correlation of resistance toward C. higginsianum with NADPH pool size, pyruvate contents, and other metabolites associated with redox poise and energy charge was evident, which fosters the hypothesis that limitations in the mETC can support resistance at post-penetration stages by improving the availability of metabolic power.